A value-based Aswaja curriculum approach to strengthen moderate Islamic character in higher education - Khalimatus Sadiyah; Ajat Sudrajat; Rukiyati Rukiyati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines the weakening internalisation of Islamic values in Islamic higher education, focusing on Nahdlatul Ulama institutions where Ahlussunnah Wal-Jama’ah (Aswaja) serves as an ideological foundation for strengthening moderate Islamic character. Using a qualitative multiple case study at Wahid Hasyim University Semarang and Balekambang Polytechnic Jepara, data were collected through in-depth interviews, participatory observation, and analysis of curriculum and institutional policy documents. The findings reveal four key patterns: Aswaja values are more strongly embedded in formal religious activities than in academic learning; institutional policies lack measurable indicators for Aswaja-based character outcomes; campus leadership plays a decisive role in shaping Aswaja institutional culture; and students tend to perceive Aswaja as an institutional identity rather than an ethical framework guiding academic practice. These findings indicate a gap between the normative vision of Aswaja and its practical implementation, resulting in symbolic and fragmented internalisation. This study concludes that strengthening moderate Islamic character requires a systemic Aswaja value-based curriculum integrating conceptual, pedagogical, and institutional dimensions, positioning Aswaja as an epistemological framework rather than merely a cultural symbol.